THU0054 Reduction of il-18 serum levels in rheumatoid arthritis during short term-treatment with infliximab. (1st June 2001) - Bombardieri, M; Pittoni, V; Conti, F; Spinelli, FR; Spadaro, A; Riccieri, V; Alessandri, C; Scrivo, R; Valesini, G
Abstract : Background: IL-18 is a recently identified cytokine thought to play a role in many autoimmune diseases including RA. Initially known as INFγ-inducing factor, IL-18 was shown to be able to exert its inflammatory actions also upregulating, at least in vitro, other cytokines such as TNFα. It has also been shown that TNFα induces the expression of IL-18 in synovial tissues, an observation which raises the possibility of a positive feedback between these two cytokines. It has recently been demonstrated that TNFα-blocking treatments in RA patients result in the down-regulation of serum levels of other proinflammatory cytokines, thus providing an additional anti-inflammatory effect. Objectives: The aim of this study was to measure serum IL-18 levels in RA patients treated with monoclonal anti-TNFα antibody (Infliximab) and to evaluate the main clinical and laboratory parameters. Methods: Ten patients with RA, non responding to DMARDs, were enrolled. Infliximab was administered i.v. at a dose of 3 mg/Kg at baseline, after 2, 6 and 14 weeks. Sera from all patients were collected before each infusion and stored at ?20°C until tested using an enzyme-linked IL-18 assay. Statistical analysis was performed using non parametric methods for paired samples. Results: Serum IL-18 levels were significantly reduced from baseline value (median/25°-75°percentile 1008/465–1676 pg/ml) after 2 weeks (185/0–1241 pg/ml, p < 0.005), 6 weeks (175/0–644, p < 0.01) and 14 weeks (59/0–437, p < 0.02). No significant decrease was observed between IL-18 levels at 2, 6 and 14 weeks. After 2 weeks ESR (p < 0.005) and CRP (p < 0.02) values were significantly reduced from baseline, while we observed a significant increase in ESR (p < 0.02) and CRP (p < 0.03) values at 6 weeks as against 2 weeks, without any significant change at 14 weeks. There was a significant decrease from baseline in both the number of tender joints (p < 0.02) and the patient global evaluation of disease activity (p < 0.02) at 6 weeks, while no correlation between serum IL-18 levels and clinical/laboratory parameter was found at any time-point. Conclusion: Our results demonstrate that anti-TNFα therapy downregulates serum IL-18 levels already after 2 weeks of treatment and maintains them significantly lower than the baseline at 6 and 14 weeks. Thus, modulation of IL-18 could contribute to the anti-inflammatory actions of TNFα-blocking treatments. Health services, economics and outcome research